Highly efficient triarylene conjugated dyes for dye-sensitized Zn2SnO4 solar cells. (October 2017) - Dou, Jie; Li, Yafeng; Xie, Fengyan; Chow, Tahsin J.; Wei, Mingdeng
Highlights: The dyes especially suitable for Zn2 SnO4 were investigated. The PSP dyes exhibited a higher efficiency of 4.68% than that of N719 and D131. The pre-calcination of Zn2 SnO4 resulted in a 17% enhancement of efficiency. The charge collection efficiency was enhanced greatly after the pre-calcination. Abstract: Zinc stannate (ZTO) is a class of ternary oxides that are known for their stable properties and high electron mobility. Also, its chemical compositions and band structures are easy to be controlled, and which is thus ideal for applications in dye-sensitized solar cells (DSCs). However, the structures of most dyes are optimized for the widely used TiO2 . Therefore, the efficient dyes that are especially suitable for ZTO are highly desired. In this study, the dyes containing phenylene-thiophenylene-phenylene bridge (PSP) were found to match well with the band structures of ZTO and could be used as efficient sensitizers for ZTO-based solar cells. Moreover, the pre-calcination temperatures have great influence on the band structures of ZTO. When ZTO nanoparticles were pre-sintered, although the adsorption amount of dyes was decreased, the charge collection efficiency was confirmed to be enhanced greatly. A cell sensitized by optimized PSP dyes exhibited a power conversion efficiency of 4.68%, which was much higher than that of widely used N719 and D131.